Survey data on orientations, boot camps, and pre-matriculation programs in schools/colleges of pharmacy - Klausner, Eytan A. (Data Brief, 2021)
A survey about orientations, boot camps, and pre-matriculation programs in schools/colleges of pharmacy was approved by the South College Institutional Review Board (IRB). The survey was sent electronically to Assistant/Associate Deans of Academic Affairs or administrators in similar positions at schools/colleges of pharmacy in October 2016. The survey was closed two months later, in December, with 50 responses. The data that was collected from the survey included characteristics and components of orientations, boot camps, and pre-matriculation programs, such as session content and the frequency sessions appeared. The survey also collected descriptive information from respondents regarding certain demographics related to their schools/colleges of pharmacy (e.g., public or private institutions, a 4-year program or a 3-year program). The data can be used by schools/colleges of pharmacy and other healthcare professions that wish to revise or establish orientations, boot camps, and pre-matriculation programs.